Kirkwood–Salsburg equation for a quantum lattice system of oscillators with many-particle interaction potentials - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
For a Gibbs system of one-dimensional quantum oscillators on a d-dimensional hypercubic lattice interacting via superstable pair and many-particle potentials of finite range, we prove the existence of a solution of the (lattice) Kirkwood–Salsburg equation for correlation functions depending on the Wiener paths. Some many-particle potentials may be nonpositive.